Antarctic daily precipitation amounts for January 1979 - July 2017 from the RACMO version 3p2 limited area atmospheric model, along with flags that indicate extreme precipitation events ... - van de Berg, Willem; van Wessem, Melchior; van de Broeke, Michiel; Turner, John; Phillips, Tony (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2019)
Two netcdf files are provided that contain daily precipitation amounts for January 1979 - July 2017 from the RACMO version 3p2 limited area, atmosphere-only model. The model is described in van Wessem, J. M., C. H. Reijmer, M. Morlighem, J. Mouginot, E. Rignot, B. Medley, and E. van Meijgaard, (2014) Improved representation of East Antarctic surface mass balance in a regional atmospheric climate model, Journal of Glaciology, 60, 761-770. The model was run over a 262 by 240 grid point domain covering Antarctica and parts of the Southern Ocean. The model was forced at the lateral boundaries by data from the European Centre for Medium-range Weather Forecasting (ECMWF) Interim reanalysis (ERA-Interim). Flags are provided for extreme precipitation events. A precipitation day was taken as a daily total of precipitation of greater than 0.02 mm. Extreme precipitation events were then taken as days when daily precipitation amount was greater than the 90th percentile of the daily precipitation values over the period ...